Análisis mediante simulación numérica de la inyección de baches surfactante/polímero para el campo Yariguí-Cantagallo operado por Ecopetrol S.A. (2015)
Yariguí-Cantagallo Field was discovered in the mid 40’s, and acquired in 1975 by Ecopetrol SA. In the month of November 2008, and due to reduced reservoir pressure, Ecopetrol decided to do an intervention, beginning by to implement secondary recovery methods. It would be made by adding water injection wells in order to maintain reservoir pressure. Is expected the fact that oil production to increase considerably. Ecopetrol began a process of evaluating the feasibility of recovery in the tertiary (chemical injection) field, in order to increase oil production. In turn, to reduce water production in producing wells.